Cultivo in vitro de duas espécies de Cattleya L.(Orchidaceae), com diferentes concentrações de auxina e citocininas - Rodrigues, Guilherme (2009)
The purpose of this study was the verification of the in vitro development of seedings of two Cattleya species: Cattleya intermedia var. alba and Cattleya bicolor , in diferent combinations of plant growth regulators, using the acid-3 - Indolbutilico (IBA) as auxin and 6-fururilamino-purina (KIN) and 6-Benzylaminapurine (6-BA) as cytokinins. The assimbióticas cultures were kept in Knudson nutritive environments (KC), supplemented by dial combinations of auxins and cytokinins with concentrations of 0,5 - 1,0 - 1,5 mg/L and kept under the continues light influence or photoperiod of 14 hours, during six months. With IBA presence and KIN or 6-BA absence occured a bigger development of Cattleya bicolor compared to C. intermédia var. alba; the C. intermédia var. alba presented an efficient development of roots and air parts in KC environment with the absence of any IBA with KIN or 6-BA combinations, determining the presence of 6-BA with a bigger pH stability in the culture environment; when the inoculated seedings supplemented with 0,5 mg/L of IBA and 1,0 mg/L of KIN, these seedings promoted the development of new Cattleya bicolor and C. intermedia var. alba roots; and for the in vitro development of C. intermedia var. alba seedings these can be inoculated in KC environment without 6-BA combinations determining the presence the addition of IBA or 6-BA and after the induction of roots and leaves, the seedings can be transferred to KC, containing only 1,0 mg/L of IBA.